Pengembangan Media Flashcard PEKARKALI (Permainan Kartu Perkalian) untuk Meningkatkan Kemampuan Literasi Matematika Siswa SD - Puput Kristiani; Wahyudi (JANACITTA, 2025)
Abstract This research and development aims to describe the media development, the level of media validity, media effectiveness, and media practicality of PEKARKALI (Multiplication Card Game) flashcards in enhancing elementary school students' mathematical literacy. The method used in this research is Research and Development (R&D) with the ADDIE development model (Analyze, Design, Develop, Implement, Evaluate). The stages in this development research include problem identification, data collection, product design, product design validation, product design revision, field trials, and evaluation. The subjects of this study were third-grade students of SD Negeri Tingkir Lor 02. Data collection techniques involved interviews, Likert scale questionnaires, and pre-test and post-test using the media. Data analysis techniques include quantitative and qualitative methods in the discussion. The validation process of this learning media was comprehensively carried out involving various experts in their fields, yielding a highly positive consensus: material experts provided a score percentage of 96.6%, media experts 93%, and learning design experts achieved a perfect score of 100%, all categorizing the media as “very high.” The effectiveness aspect of the media was statistically proven through a T-Test, which yielded a significance value (sig.) of 0.001 (p < 0.05). This result unequivocally indicates a significant increase in mathematical literacy scores, evident from the rise in the average score from 67% in the pre-test phase to 89% in the post-test phase. Furthermore, besides validity and effectiveness, this media also demonstrated a high level of practicality based on user responses: student evaluations reached 90% with “very practical” criteria, and teacher responses were even higher, at 96%, also categorized as “very practical.” Overall, these findings affirm the feasibility and appropriateness of this media in supporting the mathematical literacy learning process. Abstrak Penelitian dan pengembangan ini bertujuan untuk mendeskripsikan pengembangan media, tingkat validitas media, keefektifan media, dan kepraktisan media flashcard PEKARKALI (Permainan Kartu Perkalian) terhadap peningkatan literasi matematika siswa SD. Metode yang digunakan dalam penelitian ini adalah Research and Development (R&D) dengan model pengembangan ADDIE (Analyze, Design, Develop, Implement, Evaluate). Tahapan dalam penelitian pengembangan ini mencakup identifikasi permasalahan, pengumpulan data, desain produk, validasi desain produk, revisi desain produk, uji coba lapangan, dan evaluasi. Subjek penelitian ini adalah siswa-siswi kelas 3 SD Negeri Tingkir Lor 02. Teknik pengumpulan data dengan wawancara, angket skala likert, dan tes sebelum (pretest) dan sesudah (posttest) menggunakan media. Teknik analisis data kuantitatif dan kualitatif pada pembahasan. Proses validasi media pembelajaran ini telah dilaksanakan secara menyeluruh dengan melibatkan berbagai pakar di bidangnya, menghasilkan konteks yang sangat positif: ahli materi memberikan persentase skor 96,6%, ahli media 93%, dan ahli desain pembelajaran mencapai skor sempurna 100%, di mana kesemuanya mengukuhkan media dalam kategori “sangat tinggi”. Aspek efektivitas media terbukti secara statistik melalui Uji T yang menghasilkan nilai signifikansi (sig.) sebesar 0,001 (p < 0,05), secara tegas nilai literasi matematika, yang terlihat dari kenaikan rata-rata skor dari 67% pada tahap pretes menjadi 89% pada tahap posttes. Selain validitas dan efektivitas, media ini juga menunjukkan tingkat kepraktisan yang tinggi berdasarkan respon pengguna lapangan: penilaian siswa mencapai 90% dengan kriteria “sangat praktis”, dan respons guru bahkan lebih tinggi, yaitu 96%, juga dengan kategori “sangat praktis”, yang secara keseluruhan menegaskan kelayakan media ini dalam mendukung proses pembelajaran literasi matematika.